SCADA Sistem Pengisian dan Pengepakan Kemasan Multigrain Rice Berisi 2-3 Macam Biji-bijian - Theresia Prima Ari Setiyani; Adrian Kristoforus; Yashinta Maretyana (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2023)
The process of packing food products manually raises many problems, including inefficiency, quality of hygiene, changing the composition according to market demand, and monitoring, that are difficult to do remotely in real-time. This research builds SCADA for filling and packing Multi-grain rice packages containing 2-3 kinds of grains.The composition of the grain be filled in the package through the HMI. The conveyor moves to carry the packing bags and stops at each grain container. The rotary vane feeder of the container will rotate so that the packaging bag will be filled with grains and then glued together. The position of the packaging bag is detected by 3 pairs of photosensors. The actuator control uses a Schneider M221 PLC via ethernet port. The communication system between the I/O devices and the PLC uses a cable, while the communication between the PLC and the HMI is via the internet network.The system is capable of filling the material according to the desired composition, sealing, and packing to the number of packages. HMI feeds composition input to the system, displays animations correctly, raises an alarm when the material in the tub is running low, andÂ  record production as a daily report.